2012
DOI: 10.1037/h0093969
|View full text |Cite
|
Sign up to set email alerts
|

Blind consent? A social psychological investigation of non-readership of click-through agreements.

Abstract: Across two studies we aimed to measure empirically the extent of non-readership of clickthrough agreements (CTAs), identify the dominant social representations that exist about CTAs, and experimentally manipulate these representations in order to decrease automatic non-reading behavior and enhance contract efficiency. In our initial questionnaire study (Study 1), as predicted, the vast majority of participants reported not reading CTAs and the most prevalent social representations of CTAs contributing to non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 74 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…Psychology and bioethics show us that whilst informing and comprehension is central to the recognized definition of consent, the extent to which one can explicate sufficient risk to inform the user, in a way they understand, is an ongoing problem. Factors such as use of language [5], user prior education [26], reliance upon heuristic reasoning [4], and a predisposition to analyze risks in 'experiential' intuitive ways [30], render current approaches to informing highly problematic.…”
Section: Consent In Ubicompmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychology and bioethics show us that whilst informing and comprehension is central to the recognized definition of consent, the extent to which one can explicate sufficient risk to inform the user, in a way they understand, is an ongoing problem. Factors such as use of language [5], user prior education [26], reliance upon heuristic reasoning [4], and a predisposition to analyze risks in 'experiential' intuitive ways [30], render current approaches to informing highly problematic.…”
Section: Consent In Ubicompmentioning
confidence: 99%
“…The literature on consent draws from multiple contributing disciplines (e.g. law [2], computer science [3], psychology [26], bioethics [21], sociology and design [13]), casting consent as a conceptually complex and multifaceted issue. However, even without the additional challenges posed by ubicomp, these perspectives are siloed, disparate, epistemologically distinct and often highly theoretical, rather than applied, and as such are not immediately useful to the design of ubiquitous systems.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to understand user agreements ('Terms and Conditions' and 'Privacy Policy' statements) and their ongoing changes is a challenge for people living with dementia. These text heavy agreements are very complex, full of jargon and require a lot of time to read and interpret by end-users [56]. Unfortunately, people living with dementia suffer from progressive cognitive disabilities and can have difficulties concentrating on and interpreting long pieces of written text [32].…”
Section: Discussionmentioning
confidence: 99%
“…Consider how rarely people read EULAs before buying or using products. One study [59] found that over 80% of their participants either reported "not reading the EULA at all" or "not really reading anything." Of the remaining 20%, 16.5% described their reading behavior as "skimming."…”
Section: Unauthorized Accessmentioning
confidence: 99%